2019
DOI: 10.1002/etc.4534
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the General Threshold Model of Survival and Dose–Response Models in Simulating the Acute Toxicity of Metals to Danio rerio

Abstract: We exposed zebrafish (Danio rerio) to different concentrations of lead and cadmium, and monitored them for survival at 24, 48, 72, and 96 h. Metal toxicity was predicted and compared using the dose–response and general threshold survival models in terms of required data sets, fit performance, and applicability. Environ Toxicol Chem 2019;38:2169–2177. © 2019 SETAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…They demonstrated this by using the dataset of Nyman et al [35], in which the survival of the crustacean Gammarus pulex exposed to the azole fungicide propiconazole was assessed. He et al [36] also concluded that there was a negligible difference between the experimentally observed survival and predictions by the GUTS for zebrafish (Danio rerio) exposed to metals. Subsequently, the GUTS framework has been demonstrated to be an accurate tool for several compounds [36].…”
Section: Comparison Of Model Performancesmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated this by using the dataset of Nyman et al [35], in which the survival of the crustacean Gammarus pulex exposed to the azole fungicide propiconazole was assessed. He et al [36] also concluded that there was a negligible difference between the experimentally observed survival and predictions by the GUTS for zebrafish (Danio rerio) exposed to metals. Subsequently, the GUTS framework has been demonstrated to be an accurate tool for several compounds [36].…”
Section: Comparison Of Model Performancesmentioning
confidence: 99%
“…He et al [36] also concluded that there was a negligible difference between the experimentally observed survival and predictions by the GUTS for zebrafish (Danio rerio) exposed to metals. Subsequently, the GUTS framework has been demonstrated to be an accurate tool for several compounds [36]. However, as the EFSA [18] also discussed, doubts remain regarding the predictive power of the GUTS framework for compounds that show increased toxicity over time, such as neonicotinoids.…”
Section: Comparison Of Model Performancesmentioning
confidence: 99%